Effect of biostimulants on the chemical profile of food crops under normal and abiotic stress conditions - Salima Boutahiri; Rachid Benrkia; Babalwa Tembeni; Olusola Emmanuel Idowu; Opeyemi Joshua Olatunji (Current Plant Biology)
Biostimulants are substances/micro-organisms that have the ability to stimulate plant growth, nutrition and stress tolerance independently of their nutritional content. They are increasingly replacing the use of chemical fertilizers, which have harmful consequences for the environment. Biostimulants are derived from a variety of sources, including micro-organisms, plant extracts, algae, hydrolysates of animal or plant proteins, and humic substances. They have been tested on a variety of crops under normal and abiotic stress conditions and have succeed each time in proving their effectiveness in improving the chemical composition of plants. This improvement has a positive impact on plants' nutritional properties and resistance to stress conditions. These effects not only have positive impact on human health, but also on climate change challenges, and increasing demand for food. However, the difficulty in interpreting the results obtained from the use of biostimulants is due to their variable composition, which is not always known, making it difficult to determine their modes of action and hence their regulation. The purpose of this review is to highlight the positive effect of biostimulants on the chemical composition of food crops under normal or abiotic stress conditions. It presents an overview of chemical variability in plants and gathers studies that help clarify the effect of biostimulants. Additional studies on economic aspects, research gaps, and future prospects in the field of biostimulants are also discussed.